P NMR Observations on the Effect of the External pH on the Intracellular pH Values in Plant Cell Suspension Cultures. - Fox, G; Ratcliffe, G (1990)
(31)P nuclear magnetic resonance (NMR) spectroscopy was used to monitor the response of oil palm (Elaeis guineensis) and carrot (Daucus carota) cell suspensions to changes in the external pH. An airlift system was used to oxygenate the cells during the NMR measurements and a protocol was developed to enable a constant external pH to be maintained in the suspension when required. Phosphonoacetic acid was used as an external pH marker and the intracellular pH values were measured from the chemical shifts of the cytoplasmic and vacuolar orthophosphate resonances. In contrast to earlier studies the cytoplasmic pH was independent of the external pH over the range 5.5 to 8.0 and it was only below pH 5.5 that the cytoplasmic pH varied, falling at a rate of 0.12 pH unit per external unit. Loss of pH control was observed in response to sudden increases in external pH with the response of the cells depending on the conditions imposed. A notable feature of the recovery from these treatments was the transient acidification of the cytoplasm that occurred in a fraction of the cells and overshoot phenomena of this kind provided direct evidence for the time dependence of the regulatory mechanisms.